2019
DOI: 10.1016/j.atherosclerosis.2018.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Constipation and risk of death and cardiovascular events

Abstract: Background and aims: Constipation is one of the most frequent symptoms encountered in daily clinical practice and is implicated in the development of atherosclerosis, potentially through altered gut microbiota. However, little is known about its association with incident cardiovascular events. Methods: In a nationally representative cohort of 3,359,653 U.S. veterans with an estimated glomerular filtration rate (eGFR) ≥60 mL/min/1.73 m 2 between October 1, 2004 and September 30, 2006 (baseline period), with fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
130
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 185 publications
(138 citation statements)
references
References 39 publications
1
130
0
7
Order By: Relevance
“…37 Impact on Clinical Outcomes Constipation has been increasingly recognized as a potentially serious condition, particularly in patients with ESRD receiving PD, affecting the mechanical properties of dialysis techniques and predisposing to bacterial intestinal translocation and eventual enteric peritonitis. 76 Although little attention has been paid to the clinical impact of constipation beyond its gastrointestinal complications (e.g., diverticulitis, perforation, and peritonitis), 6,103,104 recent studies have disclosed its independent associations with the risk of several clinical outcomes, such as Parkinson's disease, 105 ESRD, 14 CV disease, [15][16][17][18] and mortality. 18…”
Section: Clinical Impact Of Constipation In Ckd Impact On Economy Andmentioning
confidence: 99%
See 3 more Smart Citations
“…37 Impact on Clinical Outcomes Constipation has been increasingly recognized as a potentially serious condition, particularly in patients with ESRD receiving PD, affecting the mechanical properties of dialysis techniques and predisposing to bacterial intestinal translocation and eventual enteric peritonitis. 76 Although little attention has been paid to the clinical impact of constipation beyond its gastrointestinal complications (e.g., diverticulitis, perforation, and peritonitis), 6,103,104 recent studies have disclosed its independent associations with the risk of several clinical outcomes, such as Parkinson's disease, 105 ESRD, 14 CV disease, [15][16][17][18] and mortality. 18…”
Section: Clinical Impact Of Constipation In Ckd Impact On Economy Andmentioning
confidence: 99%
“…Subsequently, using a cohort of 45,112 Japanese men and women aged 40 to 79 years, Honkura et al 17 reported that a lower defecation frequency was significantly associated with higher CV mortality (21% and 39% higher mortality for defecation frequency of 1 time every 2-3 days and #1 time every 4 days [vs. $1 time per day], respectively). In a recent large observational study of 3,359,653 US veterans with an eGFR $60 ml/min per 1.73 m 2 , Sumida et al 18 reported that patients with (vs. without) constipation had 11% and 19% higher incidence of coronary heart disease and ischemic stroke, respectively, and also experienced a 12% higher all-cause mortality.…”
Section: Constipation and CV Disease And Mortalitymentioning
confidence: 99%
See 2 more Smart Citations
“…В среднем около 2% людей на Земле страдают запорами, заболеваемость в среднем составляет примерно 1% в год [1]. Только треть принимающих слабительные препараты делают это по рекомендации врача, остальные -по совету знакомых, без выбора, случайно [2].…”
unclassified